2020
DOI: 10.1111/apa.15370
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation showed that stakeholders valued the support provided by the Implementing Pediatric Advance Care Planning Toolkit

Abstract: The number of children and adolescents living with life-limiting conditions has increased due to medical and technological advances. 1 These are conditions where there are no curative treatment options left or where a cure might be possible, but could still lead to a premature death. 1 The importance of communicating with children and their parents about care options is widely acknowledged. Advance care planning (ACP) is a valuable communication strategy that aligns

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(59 citation statements)
references
References 31 publications
(100 reference statements)
1
51
0
1
Order By: Relevance
“…In current research and practice in the field of PPC, there is a growing interest in strategies to anticipate the future in an adequate way [26]. Tools are developed to support families and HCPs in anticipating the future by ACP [27,28]. Our study reveals some key points that show why implementation of ACP and other strategies to anticipate the future need ongoing attention.…”
Section: Discussionmentioning
confidence: 97%
“…In current research and practice in the field of PPC, there is a growing interest in strategies to anticipate the future in an adequate way [26]. Tools are developed to support families and HCPs in anticipating the future by ACP [27,28]. Our study reveals some key points that show why implementation of ACP and other strategies to anticipate the future need ongoing attention.…”
Section: Discussionmentioning
confidence: 97%
“…Fahner et al evaluated the IMPACT pedACP toolkit using a combination of a survey, focus groups and qualitative interviews, 31 which however did not include joint discussions between parents and professionals. In accord with our data, they found that building an atmosphere of trust and engagement and honoring parental caring for the child influence parental readiness for pedACP.…”
Section: Discussionmentioning
confidence: 99%
“…An important limitation of our study is that no children undergoing palliative care treatment at time of study or their parents were included, as was the case in the study by Fahner et al 31 We chose to focus our attention on bereaved parents, as the vast majority of children in pediatric palliative care cannot be actively involved in a study on pedACP development due to age, neurological impairment, or both. 37 As children and adolescents with decision-making capacity are legally considered as akin to adults in many jurisdictions including Germany, we chose to look at their needs and support requirements concerning ACP in a separate study, which is currently underway.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using input from interviews with healthcare professionals and a review of the grey literature and the academic literature via PubMed, we developed a conceptual framework outlining the pathways through which the intervention would change desired outcomes. We then identified a pACP program in the Netherlands, called IMPACT (Implementing Paediatric Advance Care Planning Toolkit) [ 16 ], that matched the direction of the BOOST pACP program as defined by the conceptual framework. The IMPACT preparation booklets, the summary sheet and conversation structure were integrated into and adapted to the BOOST pACP program, in close collaboration with the developers of IMPACT (MK, JF).…”
Section: Methodsmentioning
confidence: 99%